Peran Kelembagaan dalam Pelaksanaan KPS Penyediaan Air Minum - Adam, Latif (Pusat Penelitian Ekonomi-LIPI, 2015)
This study analyzes the institutional role in the implementation of PPPs in the water sector. The institutional approach in this paper will be focused on the organizational structure and regulation. The purpose of this study is to map the role and institutional problems in the development of water infrastructure and analyze the important steps that can be done to strengthen the institutions in the implementation of PPP in infrastructure clean water. An analytical technique used in this study is a descriptive analysis. The analysis showed that the institutional strengthening both regulations and institutions are absolutely necessary to maximize the role and functions of the institution concerned. The working relationship between institutions that have not been harmonious and well integrated so that there is an overlap of authority in implementing PPP. Institutional strengthening with the increase of personnel resources of the central government and the regional government with capacity building through the understanding of the legal aspects, financial and other technical aspects in the preparation of the PPP contract. From the regulatory side, the PPP law is very comprehensive and experienced improvements to accommodate the dynamics. The central and local government should have the same understanding in the implementation of regulations that provide security and certainty for the private sector to invest in the water sector.